THE INFLUENCE OF FINANCIAL KNOWLEDGE AND RISK TOLERANCE ON INVESTMENT DECISION MAKING - Mubaraq, Muhammad Raihan; Anshori, Muslich; Trihatmoko, Huda (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2021)
This study aims to provide empirical evidence of the effect of financial knowledge and risk tolerance on investment decision-making. This type of research is associated research with data collection methods using survey samples. Measurement of variables in this study uses a Likert scale from 1 for strongly disagree to a scale of 5 for strongly agree. The population in this study are investors who have attended the capital market school in the Indonesian Stock Exchange, West Nusa Tenggara Representative Office, and who had a single investor identification (SID). Sampling refers to the Slovin formula with a sample size of 110 respondents. Analysis of the data in this study using multiple linear regression analysis. The results of this study indicate that financial knowledge and risk tolerance affect investment decision-making. Implications of this study for investors to pay more attention to understanding in the form of financial knowledge and recognize the type of risk tolerance that exists in investors in making investment decisions in the capital market.JEL: G11, G14, G32, G41